2012
DOI: 10.1111/j.1365-2559.2011.04140.x
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of infrared microspectroscopic imaging for histopathology of the uterine cervix

Abstract: This imaging technique has potential as a new method for tissue characterization; however, the recognition accuracy does not justify a pathologist-independent tissue analysis, and the application is only possible in combination with concomitant conventional histopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…7 Based on this more recently, the concept of spectral histopathology/cytology has been established where morpho-histological features of cells and tissues have been deciphered using imaging approaches. 814 In the same context, we also recently demonstrated the concept of spectral bar coding for differentiating normal from cancerous colon tissues. 15 IR imaging can be performed in the conventional transmission mode (IR-T) in which the IR light is absorbed by a thin tissue section in its path, transflection mode in which the IR light is transflected by a reflecting surface onto which the tissue is placed, or the less conventional IR attenuated total reflection mode (ATR-IR).…”
Section: Introductionmentioning
confidence: 83%
“…7 Based on this more recently, the concept of spectral histopathology/cytology has been established where morpho-histological features of cells and tissues have been deciphered using imaging approaches. 814 In the same context, we also recently demonstrated the concept of spectral bar coding for differentiating normal from cancerous colon tissues. 15 IR imaging can be performed in the conventional transmission mode (IR-T) in which the IR light is absorbed by a thin tissue section in its path, transflection mode in which the IR light is transflected by a reflecting surface onto which the tissue is placed, or the less conventional IR attenuated total reflection mode (ATR-IR).…”
Section: Introductionmentioning
confidence: 83%
“…The exploration of label-free diagnostic methods is a highly sought after area of research and mid-IR spectral imaging is a promising tool in this regard. This is now well documented where several studies have shown the potential of mid-IR imaging as a diagnostic tool applied to various types of cancer [9,10,[36][37][38]. To precisely interpret the biomolecular changes either in a manual or an automatic manner, it is essential to have highly resolved images.…”
Section: Characterization Of Tissue Featuresmentioning
confidence: 99%
“…Fourier‐transform infrared (FTIR) spectral imaging, which allows characterization of histological structures of a tissue, is an innovative, non‐destructive, and label‐free diagnostic method. In oncology, this method can be used for discriminating between normal and cancerous tissues from different organs, such as brain , skin , colon , lung , breast , prostate or cervix .…”
Section: Introductionmentioning
confidence: 99%
“…method. In oncology, this method can be used for discriminating between normal and cancerous tissues from different organs, such as brain [1], skin [2], colon [3,4], lung [5,6], breast [7], prostate [8] or cervix [9].…”
Section: Introductionmentioning
confidence: 99%